Bioprosthetic heart valves of the future. (21st January 2014) - Manji, Rizwan A.; Ekser, Burcin; Menkis, Alan H.; Cooper, David K.C.
Abstract Glutaraldehyde‐fixed bioprosthetic heart valves (GBHVs), derived from pigs or cows, undergo structural valve deterioration (SVD) over time, with calcification and eventual failure. It is generally accepted that SVD is due to chemical processes between glutaraldehyde and free calcium ions in the blood. Valve companies have made significant progress in decreasing SVD from calcification through various valve chemical treatments. However, there are still groups of patients (e.g., children and young adults) that have accelerated SVD of GBHV. Unfortunately, these patients are not ideal patients for valve replacement with mechanical heart valve prostheses as they are at high long‐term risk from complications of the mandatory anticoagulation that is required. Thus, there is no "ideal" heart valve replacement for children and young adults. GBHVs represent a form of xenotransplantation, and there is increasing evidence that SVD seen in these valves is at least in part associated with xenograft rejection. We review the evidence that suggests that xenograft rejection of GBHVs is occurring, and that calcification of the valve may be related to this rejection. Furthermore, we review recent research into the transplantation of live porcine organs in non‐human primates that may be applicable to GBHVs and consider the potential use of genetically modified pigs as sources of bioprosthetic heart valves.